Congruence of Aspirations of Rural Youth With Expectations Held by Parents and School Staff - Joyce Ley; Steven Nelson; Svetlana Beltyukova (Journal of Research in Rural Education, 1996)
This study explored the relationship of the aspirations of rural high school students with the expectations held by their parents and teachers. A sample ofeleventh and twelfth grade studentsfrom 21 rural high schools in 21 states, along with their parents and teachers, revealed significant coefficients ofconcordance among the three groups' expectationsfor adulthood. While expectationsfor personal and economic success were highly prized, community-minded goals for civic responsibility were ascribed far less importance. Implications for rural schools and communities are discussed.